Lexical approach activities to increase students basic vocabulary - Molina Ayala, Elvia Teresa (2016)
Lexical approach plays a key role in vocabulary increase because students can combine different words in order to develop speaking skill by using collocations. The main objective of this investigation is to determine the influence of applying lexical approach in 8th graders at “Lenin School” Educative Unit to improve vocabulary learning. The instrument used in this investigation was a questionary used as pre-test and post-test. It consisted on twenty collocation items chose from students‟ book “Our Little world”. Pre- test was applied to measure students‟ level of knowledge vocabulary….